Oxidative stress response in neural stem cells exposed to different superparamagnetic iron oxide nanoparticles - Pongrac, Igor M; Pavičić, Ivan; Milić, Mirta; Brkić Ahmed, Lada; Babič, Michal; Horák, Daniel; Vinković Vrček, Ivana; Gajović, Srećko (International journal of nanomedicine, 2016)
Biocompatibility, safety, and risk assessments of superparamagnetic iron oxide nanoparticles (SPIONs) are of the highest priority in researching their application in biomedicine. One improvement in the biological properties of SPIONs may be achieved by different functionalization and surface modifications. This study aims to investigate how a different surface functionalization of SPIONs - uncoated, coated with d-mannose, or coated with poly-l-lysine - affects biocompatibility. We sought to investigate murine neural stem cells (NSCs) as important model system for regenerative medicine. To reveal the possible mechanism of toxicity of SPIONs on NSCs, levels of reactive oxygen species, intracellular glutathione, mitochondrial membrane potential, cell-membrane potential, DNA damage, and activities of SOD and GPx were examined. Even in cases where reactive oxygen species levels were significantly lowered in NSCs exposed to SPIONs, we found depleted intracellular glutathione levels, altered activities of SOD and GPx, hyperpolarization of the mitochondrial membrane, dissipated cell-membrane potential, and increased DNA damage, irrespective of the surface coating applied for SPION stabilization. Although surface coating should prevent the toxic effects of SPIONs, our results showed that all of the tested SPION types affected the NSCs similarly, indicating that mitochondrial homeostasis is their major cellular target. Despite the claimed biomedical benefits of SPIONs, the refined determination of their effects on various cellular functions presented in this work highlights the need for further safety evaluations. This investigation helps to fill the knowledge gaps on the criteria that should be considered in evaluating the biocompatibility and safety of novel nanoparticles.
Keywords: magnetické nanočástice; statická elektřina; membránové potenciály; DNA Damage; Neural Stem Cells; Antioxidants; genotoxicity; Nanoparticles; reaktivní formy kyslíku; Static Electricity; poškození DNA; myši inbrední C57BL; Hydrodynamics; Oxidative Stress; membránový potenciál mitochondrií; Ferric Compounds; Membrane Potentials; biocompatibility; antioxidancia; Reactive Oxygen Species; oxidative stress; zvířata; železité sloučeniny; Dextrans; Magnetite Nanoparticles; nervové kmenové buňky; viabilita buněk; nanočástice; Cell Survival; hydrodynamika; murine neural stem cells; Membrane Potential, Mitochondrial; oxidační stres; dextrany; superparamagnetic iron oxide nanoparticles; Mice, Inbred C57BL; Animals